Rosendo M. Mejica a bio-bibliography - Ledesma, Teresita R.; Hidalgo, Namnama P.; Linab, Clara L. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1980)
This special problem deals with the bio-bibliography of Rosendo M. Mejica, a pioneer printer-publisher in Hiligaynon, a journalist, a public official, a labor leader, and a philanthropist. It describes the man's contributions to the dissemination of Ilongo thought and culture and presents such contributions through a systematic organization of the Mejica Collection. Considered a vital link to the rich Ilongo past, the collection covers the years from 1913-1941. It consists of issues of the Makinaugalingon, the oldest and one of the most enduring vernacular newspapers in Iloilo, imprints of the Makinaugalingon Press, correspondence, clippings, printed matter, biographical features, memorials, memorabilias, greeting cards, scrapbooks, albums, invitations and programs, photographs, and family records.
The study covers a biographical sketch of Rosendo M. Mejica, a brief history of the Makinaugalingon newspaper and its press with an annotated bibliography of the Makinaugalingon imprints, and a register of the collection.
This bio-bibliographical study is an endeavor aimed at making a valuable collection known and available to the reading public.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Makinaugalingon (Periodical); Mejica, Rosendo M